2014
DOI: 10.1016/j.brainres.2013.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Features and timing of the response of single neurons to novelty in the substantia nigra

Abstract: Substantia nigra neurons are known to play a key role in normal cognitive processes and disease states. While animal models and neuroimaging studies link dopamine neurons to novelty detection, this has not been demonstrated electrophysiologically in humans. We used single neuron extracellular recordings in awake human subjects undergoing surgery for Parkinson disease to characterize the features and timing of this response in the substantia nigra. We recorded 49 neurons in the substantia nigra. Using an audito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
2
17
1
Order By: Relevance
“…Additionally, we found that the degree of coordination of the activity of SN neurons with frontal theta frequency oscillations was predictive of successful memory formation. Although previous work shows that human SN neurons respond to reward prediction errors [ 14 ] and infrequent sounds in an odd-ball paradigm [ 16 ], our data are, to our knowledge, the first study describing SN neuronal activity during declarative memory formation in humans.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Additionally, we found that the degree of coordination of the activity of SN neurons with frontal theta frequency oscillations was predictive of successful memory formation. Although previous work shows that human SN neurons respond to reward prediction errors [ 14 ] and infrequent sounds in an odd-ball paradigm [ 16 ], our data are, to our knowledge, the first study describing SN neuronal activity during declarative memory formation in humans.…”
Section: Discussionmentioning
confidence: 65%
“…Studying how SN/VTA dopaminergic neurons signal reward and reward expectation errors [ 12 14 ] has revealed a mechanistic understanding of the role of the SN/VTA in classical conditioning and reinforcement learning [ 15 ]. In addition, in humans, SN neurons also respond to infrequent sounds in an odd-ball paradigm [ 16 ] and encode decision outcomes [ 17 ]. In contrast, little is known about the role of SN/VTA in the acquisition of declarative memories.…”
Section: Introductionmentioning
confidence: 99%
“…While the neural mechanisms underlying this phenomenon remain poorly understood, some studies have implicated the attentional M3 (or P3 in EEG studies) signal in association with the TOE (Shapiro et al 2006;Hairston and Nagarajan 2007). Indeed, recent findings by our group have implicated midbrain DA neurons underlying the M3/P3 signal in an auditory oddball task (Mikell et al 2014). The TOE may thus be a reflection of greater attentional resources being devoted to the more recent stimulus.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, recent findings by our group have implicated midbrain DA neurons underlying the M3/P3 signal in an auditory oddball task (Mikell et al. 2014). The TOE may thus be a reflection of greater attentional resources being devoted to the more recent stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…102 This biphasic response was recently replicated in humans. 82 These phasic changes reverberate within the circuit, and, at higher cortical levels (or, as Kapur puts it, the "mind level"), the net result of all of this signal integration is an assignment of relative salience to a stimulus. 53 In psychosis, it is proposed that dysregulation of the tonic-phasic dopaminergic system results initially in misattributions of reward to stimuli that would otherwise be ignored, resulting in aberrant salience at those higher cortical levels, and finally manifesting clinically as the positive symptoms of schizophrenia, including delusions and hallucinations.…”
mentioning
confidence: 99%